KARAKTERISTIK DAN KLASIFIKASI ANAK BERKEBUTUHAN KHUSUS SECARA MENTAL EMOSIONAL DAN AKADEMIK - Olfa Seviona Putri; Puti Artistia; Nuhaliza Nurhaliza; Opi Andriani (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2024)
This research aims to determine the characteristics of students with special needs, in inclusive schools. The methods used were observation, interviews, and documentation, after which the data was analyzed descriptively and qualitatively. Social and communication development is the most important disorder, as in normal individuals, disorders of verbal intelligence or language and difficulties in continuously renewing behavior, desires, pleasures, and habits. Based on interview findings, observations, and literature, it shows that children with special needs show characteristics in the areas of communication, social interaction, sensory abilities, playing styles, behavior, and feelings. the child with special needs show characteristics in the areas of communication, social interaction, sensory abilities, play styles, behavior, and emotions.